Evaluation of anesthesia management, feasibility and efficacy of peroral endoscopic myotomy (POEM) for achalasia performed in the endoscopy unit - Yang, Dennis; Pannu, Davinderbir; Zhang, Qing; White, Jeffrey D.; Draganov, Peter V. (Endoscopy International Open, 2015)
Introduction: Data on anesthesia management and outcomes associated with peroral endoscopic myotomy (POEM) performed exclusively in the endoscopy unit are limited. In this prospective study, we evaluated the safety of anesthesia management, and the feasibility and efficacy of POEM performed exclusively in the endoscopy unit. Methods: A single-center prospective study of consecutive patients with achalasia treated with POEM in an endoscopy unit was performed. Safety of anesthesia management and POEM were determined by procedure-related adverse events. Feasibility was assessed by completion rate. Short-term efficacy was established by clinical success (Eckardt score ≤ 3) and by comparing Eckardt and dysphagia scores before and after POEM. Results: Patients (n = 52) underwent POEM under general anesthesia with endotracheal intubation and positive pressure ventilation. Aspiration was prevented by keeping patients on a clear liquid diet before the procedure without requiring a prior esophagogastroduodenoscopy for esophageal content clearance. POEM completion rate was 96 % (50/52 patients). There was no post-POEM bleeding. Postprocedure leak was observed in one patient (3 %). Four patients (7.7 %) experienced mucosal injury, three of them were treated uneventfully endoscopically and one required laparoscopic repair. Clinical success was achieved in 88 % of patients. There was a significant decrease in the mean Eckardt score (8.1 to 1.4) and dysphagia score (2.4 to 0.4) (P < 0.0001) at the one month follow up after POEM. Conclusion: Anesthesia management of POEM is safe in the endoscopy unit and aspiration can be prevented without requiring prior esophagogastroduodenoscopy for esophageal content clearance. Overall, POEM performed by a gastroenterologist in the endoscopy unit was feasible and effective for the treatment of achalasia.